Single junction solar cell employing strain compensated GaAs0.965Bi0.035/GaAs0.75P0.25 multiple quantum wells grown by metal organic vapor phase epitaxy - Kim, Honghyuk; Kim, Kangho; Guan, Yingxin; Lee, Jaejin; Kuech, Thomas F.; Mawst, Luke J. (Applied Physics Letters, 2018)
Single junction solar cells employing 30-period and 50-period GaAs0.965Bi0.035/GaAs0.75P0.25 (Eg ∼ 1.2 eV) multiple quantum wells (MQWs) as base regions were grown by metal organic vapor phase epitaxy. Room temperature photoluminescence measurements indicated a peak spectral emission at 1.18 eV, and the spectral dependence of the external quantum efficiency measured from the fabricated devices shows the extended absorption edge relative to that of GaAs. The fabricated devices with anti-reflection coating employing a 50-period MQW structure exhibit 23% improvement in the conversion efficiency, 4% in the open-circuit voltage, 9% in the short-circuit current density, and 9% in the fill factor, compared to those from the devices employing a 30-period MQW structure in the base region, under AM1.5 direct illumination.
Keywords: Direct illumination; External quantum efficiency; Metal-organic vapor phase epitaxy; Room-temperature photoluminescence; Single junction solar cells; Spectral dependences; Spectral emission; Strain-compensated